Preliminary Development of a Culturally Adapted Questionnaire on Mental Health Literacy for Chinese Junior High School Students - Chen S; Wang W; Li Y (Psychology Research and Behavior Management)
Shen Chen,1 Wei Wang,2 Yongxin Li2 1School of Teacher Education, Heze University, Heze, Shangdong, People’s Republic of China; 2Institute of Psychology and Behaviour, Henan University, Kaifeng, Henan, People’s Republic of ChinaCorrespondence: Yongxin Li, Email liyongxin@henu.edu.cnPurpose: Mental health literacy is a crucial factor in promoting adolescent mental health. However, existing mental health literacy assessment tools may not fully capture the unique psychological developmental characteristics of Chinese junior high school students. This study developed a culturally adapted measurement tool for assessing mental health literacy among this population.Methods: This study involved three stages: (1) item pool construction using a literature review and expert evaluation procedure (n = 8), (2) item selection through item and exploratory factor analyses of the initial item pool (n = 510), and (3) psychometric indicator evaluation based on reliability and validity analyses.Results: The resulting Mental Health Literacy Questionnaire for Junior High School Students consists of 30 items across three dimensions: knowledge, attitude, and behavioral tendencies. Psychometric analysis demonstrated strong internal consistency (Cronbach’s α = 0.93, KR20 = 0.90, McDonald’s ω = 0.94, r of test-retest reliability = 0.88) and satisfactory content and construct validity.Conclusion: This culturally relevant and psychometrically sound instrument can be used to accurately assess and intervene in mental health literacy among Chinese junior high school students. The tool’s development followed rigorous methodological standards; it can be a valuable resource for researchers and practitioners in the field of adolescent mental health.Keywords: mental health literacy, questionnaire development, junior high school students, mental health education